HOW OPEN INNOVATION IMPLEMENTATION IN DIGITAL ENTERPRISES INFLUENCES INDONESIA GOVERNMENT POLICY - Yuana, Rivira; Prasetio, Eko Agus; Syarief, Rizal; Suroso, Arif Imam; Arkeman, Yandra (CosmoGov: Jurnal Ilmu Pemerintahan, 2022)
The nature of new business innovation activities is increasingly scattered, multidisciplinary, cross-border, cross-institutional, and cross-temporal. The culture influences the commitment to open innovation. The organizational culture is a vital factor in the success of radical innovation and integrating internal organizational structures, policies, and partnerships. The paradigm shift from closed to open innovation has been used in various business relationships.The research objectives are determining the primary factor of open innovation success in Indonesia based on digital enterprise experiences and the extent to which the government's participation becomes meaningful and results in adaptive corporate policy.The study will be qualitative and inductive, utilizing multiple case studies. Due to the epidemic period, in-depth interviews with senior management were conducted through video conferences and private messaging. The research will employ a literature review and an expert interview to ascertain how digital enterprise cooperation contributes to long-term growth. The result shows how the O.I. strategy implemented in digital firms influences government policy.The Indonesian government may enlist the assistance of international organizations or multinational corporations to facilitate organizational reforms necessary to create an open innovation-friendly culture. Goverment businesses require specialized staff to reap the benefits of present legislation.gb777